Analisis Usaha Sapi Perah Kembar di Kecamatan Lembang Kabupaten Bandung Jawa Barat (BUSINESS OF DAIRY COW TWIN IN LEMBANG DISTRICT, BANDUNG REGENCY, WEST JAWA) - Rusdiana, Supardi; Praharani, Lisa (Jurnal Veteriner, 2020)
The purpose of this study was to determine the analysis of twin dairy cattle business in Lembang District, Bandung Regency, West Java. The study used a metoda survey of 25 farmers in the Corner Village and 25 in Sunterjaya Village, Lembang District, Bandung Regency by using interviews and filling in the questionnaire. Primary data and secondary data are then analyzed. The results of the study show that, the average ownership of dairy cows is 4.40 head/farmers. Net income of farmers is IDR 45,591 million/year, equivalent to 3.79 million/ month, B/C 1.78. The While in Sunterjaya Village has 5.28 head/farmer. Net income of farmers is IDE. 38,808 million/year,white to 3.32 million/year, B/C 1.77. Dairy business with a scale of 5-10 head/ farmer, economic value will be proportional to the cost and labor spent for one year. The difference in calf sale value of IB-TE and IB results in B/C ratio > 1, economically the twin calves of IB-TE results are feasible to be maintained and maintained.